The Role of Emotional Intelligence and Self-Leadership in Entrepreneurial Intentions of University Students - M. Wildhan Ar Mawardi; Nova Mardiana; Lis Andriani HR (Harmony Management: International Journal of Management Science and Business, 2025)
Entrepreneurship plays a crucial role in driving economic growth, with individual entrepreneurial intentions serving as a key supporting factor. Despite this, student involvement in entrepreneurial endeavors remains relatively low. This research seeks to examine how emotional intelligence and self-leadership influence entrepreneurial intentions among students at the University of Lampung. Employing a quantitative method with a causal approach, the study gathered primary data through questionnaires distributed to 183 sixth-semester students across various faculties. The research instruments underwent validity, reliability, and normality testing, and the data were analyzed using multiple linear regression. The findings confirmed the proposed hypotheses. Based on these results, the study recommends that higher education institutions, particularly the University of Lampung, implement character development initiatives and foster a positive student mindset. It also suggests creating more opportunities for reflection and open dialogue, incorporating problem-based learning models, and providing training in persuasive communication and soft skills. Furthermore, it emphasizes the importance of enhancing entrepreneurship curricula with practical experiences such as business incubators and simulations, while also improving student access to entrepreneurial support systems, including funding, mentoring, and market networks. These measures aim to boost student confidence in launching businesses and to strengthen the campus entrepreneurial ecosystem.